Pelaksanaan Kegiatan Pengembangan Diri Seni Tari Di SMP-SDI Silungkang - Deliziani Deliziani; Fuji Astuti; Nerosti Nerosti (SENDRATASIK UNP, 2019)
This study aims to describe the implementation of dance development activities in SMP-SDI Silungkang. The type of research is qualitative research by usingdescriptive method of analysis. The objects in this study were 23 students consisting of grade VII and grade VIII at SMP-SDI Silungkang. The instrument used in this study was the researchers themselves and supported by observation, documentation and interviews. The types of data in this researcher were primary data and secondary data. In data collection used secondary techniques. The technique of data collection was done by means of library studies, observation, interviews and documentation. The results of the study showed that the implementation of the dance development activities in SMP-SDI Silungkang ran well. Although, self-development activities in coaching were assisted by the teachers of Communication and Information Technology (ICT). However, the results  can be achievedwell. This was also supported by thestudents’ interest to improve their self-development of dance in the school.